Training Of Penjasorkes Teachers In Efforts To Increase Extracurricular Activities Basic School Athletics As A Sub-District Padang Utara - Arsil Arsil; Hendri Neldi; Rosmawati Rosmawati; Atradinal Atradinal (Jurnal Humanities Pengabdian Kepada Masyarakat, 2019)
Education is a conscious and planned effort to create an atmosphere of learning and learning process so that students actively develop their potential to have spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves, society, nation, and state. Through physical education, it is expected to spur student growth and development. In addition, students are expected to have basic abilities and skills and improve physical fitness in daily life. One of the activities at school which is an effort to improve the ability of students in extracurricular activities especially the athletics branch. One of the material is athletic extracurricular is that students can recognize and perform basic movements that are useful as the basis of various physical activities in addition to being useful for students in developing various forms of motion in play. In connection with the lack of implementation of extracurricular activities, especially those related to athletic material at this time, it is, therefore, necessary to conduct training in an effort to improve athletic extracurricular implementation activities for elementary school Physical Education teachers in Padang Utara District, Padang City.